MEASURES DIRECTED TO PREVENTION OF IMPORTATION AND DISSEMINATION OF SEVERE ACUTE RESPIRATORY SYNDROME (SARS) AT AMURSKAYA PROVINCE TERRITORY - G. G. Onishchenko; V. T. Smirnov; N. N. Zhukova; E. I. Shmelev; V. A. Pivovarov; O. F. Goryachkina (Acta Biomedica Scientifica, 2020)
A complex of organizingmethodical, medical preventive and antiepidemic measures both at the frontier passing points and on the whole Amurskaya Province prior to detection of a SARS case in Blagoveshchensk City and from the moment of the disease registration to prevent further dissemination of this infection is represented.